Characteristics of overlap syndrome in Mexican patients. - Claudia G. Solis-Hernandez; Marycamen Alegria-Ovando; Kenia M. Bastida-Guadarrama; Viridiana Lopez-Ladron-de-Guevara; Maria F. Higuera-de-la-Tijera; Jose L. Perez-Hernandez (Annals of Hepatology)
Introduction and Objectives: The overlap syndrome combines two or more autoimmune liver diseases such as: autoimmune hepatitis, primary biliary cholangitis and primary sclerosing cholangitis, in Mexico there is little information about this disease. Objective: To describe the characteristics of the Mexican population with overlap syndrome treated at the liver clinic of the General Hospital of Mexico. Materials and Patients: This is a retrospective, observational and analytical study in which records of patients with ADHD who met overlapping criteria (two or more hepatic autoimmune diseases) between 2020 and 2024 were reviewed to evaluate demographic variables and their presentation. Descriptive statistics with measures of central tendency and dispersion were used using SPSS 25.0. Liver enzymes AST, ALT, GGT, in addition to BT and FA of EHAI, CBP and CEP compared to CEP+EHAI were compared with Student's t-test for independent groups. Values are expressed as means and standard deviations. The Z test for contingency tables for difference of proportions with Bonferroni correction was used to compare the percentages of the degree of fibrosis among the four groups (EHAI, CBP, CEP and CEP+EHAI). A significance level of less than 5% was considered in all tests. Results: A total of 256 patients with AHD were evaluated, of whom 55 (21.4%) were found to be compliant for overlap syndrome. Of these, 93.6% were female and 7.3% male, with a mean age of 51.89 ± 12.72 years (range: 50.34-53.44). The most common phenotype was CBP/HAI (73.2%). The most frequent autoimmune comorbidities were hypothyroidism, rheumatoid arthritis, Sjögren's syndrome and systemic sclerosis. 32.1% had grade F3 fibrosis and 16.3% cirrhosis, Child A 12.5%, Child B 62.5% and Child C 25%. A higher proportion of fibrosis was observed in F2 and F3 for overlap syndrome compared to EHAI. Regarding enzymatic tests, significant differences were found in GGT (183.5±254.5 vs. 318.5±232.8) and AF between EHAI and overlap syndrome. The most frequent decompensation was variceal gastrointestinal bleeding in 62.5%, and three patients were transplanted. Conclusions: Overlap syndrome is an uncommon entity, frequent in women, which is usually associated with other autoimmune pathologies. It is associated with more severe results in liver biochemical tests, especially in GGT and AF levels, as well as with a higher degree of fibrosis.